The Role of Digital Competency Improving Employees Performance at CV Dwipa Semesta Indonesia - Syafira Alaina; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
Digital Competency is currently the main role to adapt, compete, and develop in the ever-evolving digital era. This study aims to analyze the role of employee digital competencies by identifying the dimensions of digital competencies that contribute the most to improving employee performance. Using a qualitative design, this research was conducted at CV Dwipa Alam Semesta Indonesia from October 2024 to January 2025. The research sample consisted of 5 informants selected based on their positions and obligations to assess, namely HRD, head of order department, head of marketing, head of external and internal relations of the company, and HR staff. Primary data were collected through interviews, deep interviews, observations, and field surveys, then analyzed using the Miles and Huberman model. The results of the study show that employees’ digital abilities vary, and the development of digital competencies is carried out through formal training and self-learning. Employees view technology problem-solving as a challenge that enriches learning, and the learning by doing method is considered relevant. The ability to read data is also considered good, with continuous learning individually and in teams.